2017
DOI: 10.1177/1538574417740057
|View full text |Cite
|
Sign up to set email alerts
|

Outcome After Crossing Femoropopliteal Chronic Total Occlusions Based on Optical Coherence Tomography Guidance

Abstract: In our experience, the Ocelot system would appear to be a safe and effective tool for increasing the applicability of endovascular techniques. However, the midterm results did not show drastic improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…The Ocelot catheter has shown early clinical results suggestive of a viable treatment option of chronic SFA occlusions with crossing success in 72% of cases and up to 97% with the addition of an assist re-entry device (2,7). In our cohort we encountered a 69% cross rate which was similar to those previously reported in the literature (7,9). Although there was no significant difference between the intima-media thickness or cross sectional plaque area of patients with successfully crossed and uncrossed SFA lesions, the grayscale median differed significantly between patients with uncrossed and crossed superficial femoral arteries at the proximal cap of the lesion.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The Ocelot catheter has shown early clinical results suggestive of a viable treatment option of chronic SFA occlusions with crossing success in 72% of cases and up to 97% with the addition of an assist re-entry device (2,7). In our cohort we encountered a 69% cross rate which was similar to those previously reported in the literature (7,9). Although there was no significant difference between the intima-media thickness or cross sectional plaque area of patients with successfully crossed and uncrossed SFA lesions, the grayscale median differed significantly between patients with uncrossed and crossed superficial femoral arteries at the proximal cap of the lesion.…”
Section: Discussionsupporting
confidence: 89%
“…Physicians can use OCT to image arterial structures and plaque morphology to guide treatment during revascularization procedures (7). Studies have demonstrated that the Ocelot catheter can be utilized safely and effectively to cross TASC D lesions (7,8). The CONNECT II trial demonstrated a 97% total cross rate with a 72% cross rate using the Ocelot catheter alone (2).…”
Section: Introductionmentioning
confidence: 99%
“…Most articles (n = 10) reported data concerning the performance and efficacy of the application of OCT in therapeutic means. [36][37][38][39][40][41][42][43][44][45] One article 46 discussed the decrease in fluoroscopic exposure when comparing OCT and other atherectomy devices, and another discussed a unique case scenario where the use of OCT to prevent bailout stenting. For the 10 articles, population sizes range from 1 to 272 lesions.…”
Section: Oct For Intervention Of Padmentioning
confidence: 99%
“…The femoropopliteal segments were studied the most (n = 6), [36][37][38][39][40][41] while there was only one study involving iliac arteries. 45 Two studies 40,44 did not report on what type of OCT-related device was used, but all of the remaining studies used the Ocelot catheter, 38,39,[41][42][43]45 and two other studies used Pantheris concomitantly. 36,37 The mean lesion length treated ranged from 50mm to 205mm.…”
Section: Oct For Intervention Of Padmentioning
confidence: 99%
See 1 more Smart Citation